The production cost of biological material for introducing to fattening in the swine farms - Rodica Chetroiu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
The paper meets the pork producers, in terms of identifying the cost elements for biological material introduced at fattening, which is one of the most important categories of variable expenditures. In the specialized swine breeding systems (breeding farms), the first product value quantifiable is the piglet weaned. The cost elements that can be showed refers to the cost of maintenance and feeding of the sow during pregnancy and lactation, plus the cost of the same sows from weaning until the next fecund insemination. To these are added the investment for the feed consumed by piglet and its maintenance cost until the weight at that it can be introduced for fattening (25 kg). The paper presents an analysis of the main indicators reflecting the production cost of the piglet; thus, the highest share in the total expenditures are the fodder costs (66.7%), followed by biological material costs (share of insemination and maintenance costs for the gilt until weaning) representing 10.5%.
Keywords: Q12; Q16; 330; meat; pork; expenditures; cost